2008
DOI: 10.1063/1.2996578
|View full text |Cite
|
Sign up to set email alerts
|

Electronically patterning through one-dimensional nanostripes with high density of states on single-crystalline Al2O3 domain

Abstract: Self-assembled one-dimensional nanostripes on the single-crystalline Al2O3 domains are found to be the nucleation sites of nanoparticles through an enhanced density of states observed by the scanning tunneling microscopy and spectroscopy. Bias-dependent topographic images and the conductivity spectra indicate that these nanostripes have both enhanced occupied and unoccupied states within the oxide bandgap. These more metallic nanostripes have stronger electronically trapping ability than the oxide domain, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 28 publications
3
9
0
Order By: Relevance
“…It can be seen that the stripe spacing is about 3 nm and the stripe height is about 1.2 Å . These observations are consistent with the earlier studies under the similar oxidation condition, and more details can be found from the results by Hsu et al 18 The stripe spacing of 3 nm is much larger than that (i.e., stripe spacing of 6 Å ) for oxide stripes formed by first oxidizing the NiAl(100) at room temperature followed by vacuum annealing at 750 C. In addition, the double-row stripes observed here from the room-temperature oxidation followed by annealing at 750 C are surrounded by clean surface areas, instead of oxide domains that Hsu et al 18 observed from the oxidation at the high temperature. This is further supported by the LEED pattern as shown in Fig.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…It can be seen that the stripe spacing is about 3 nm and the stripe height is about 1.2 Å . These observations are consistent with the earlier studies under the similar oxidation condition, and more details can be found from the results by Hsu et al 18 The stripe spacing of 3 nm is much larger than that (i.e., stripe spacing of 6 Å ) for oxide stripes formed by first oxidizing the NiAl(100) at room temperature followed by vacuum annealing at 750 C. In addition, the double-row stripes observed here from the room-temperature oxidation followed by annealing at 750 C are surrounded by clean surface areas, instead of oxide domains that Hsu et al 18 observed from the oxidation at the high temperature. This is further supported by the LEED pattern as shown in Fig.…”
Section: Resultssupporting
confidence: 93%
“…The height of the double-row stripes is measured to be about 0.8 Å , which is close to the one observed on the oxide formed with 1 L oxygen exposure. It should be noted that the measured heights of the oxide stripes can vary with the bias voltage, 18,20 but it is also found that the height is largely independent of the bias measured in our experiments ranging from À0.5 V to À1.0 V. The double-row stripes are formed from the high-temperature annealing at 750 C under vacuum, which suggests that these fine stripes represent an ordered and stable oxide phase. The formation of oxide stripes was also observed by oxidizing a clean NiAl(100) surface directly at a high temperature, but their structure features are found to be different from the results described above.…”
Section: Resultssupporting
confidence: 50%
See 2 more Smart Citations
“…Aluminum oxide thin films have important applications in microelectronics, protective coatings, and catalysis. In particular, the formation of aluminum oxide on NiAl substrates has been studied extensively owing to its important applications in harsh environments ranging from high‐temperature materials in propulsion systems and gas turbine engines to ambient‐temperature reactions, such as surface catalysts and electronic metallization . The aluminum oxides on NiAl(100) were typically formed by directly oxidizing a clean NiAl(100) surface at a high temperature (typically around 727°C or above) or by exposing a clean NiAl(100) surface to oxygen gas at room temperature followed by annealing at a high temperature, both of which would result in fully‐ or partially crystallized oxides .…”
Section: Introductionmentioning
confidence: 99%